2014
DOI: 10.1007/s00128-014-1444-x
|View full text |Cite
|
Sign up to set email alerts
|

The Heterologous Expression of the Iris lactea var. chinensis Type 2 Metallothionein IlMT2b Gene Enhances Copper Tolerance in Arabidopsis thaliana

Abstract: Iris lactea var. chinensis (I. lactea var. chinensis) is a widely adapted perennial species with a high level of copper tolerance. To evaluate the role of metallothioneins (MTs) in copper tolerance in I. lactea var. chinensis, a full-length cDNA homologue of MT2, designated IlMT2b (GenBank accession No. AB907788), was cloned using the RACE-PCR method. The expression level of IlMT2b in the leaves and roots of I. lactea var. chinensis was induced in response to copper (Cu) treatment. Ectopic expression of IlMT2b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…To date, plant MTs have been widely characterized, exhibiting different tissue-specific expression patterns [8,14,49,50,51,52]. For example, AtMT1A and AtMT2B were predominantly expressed in roots and leaves, while AtMT2A and AtMT3 were highly expressed in roots and young leaves [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, plant MTs have been widely characterized, exhibiting different tissue-specific expression patterns [8,14,49,50,51,52]. For example, AtMT1A and AtMT2B were predominantly expressed in roots and leaves, while AtMT2A and AtMT3 were highly expressed in roots and young leaves [14].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, plants have evolved a suite of mechanisms involving the chelation and sequestration of heavy metals by various amino acids, organic acids, phytochelatins (PCs) and metallothioneins (MTs) [3,4]. These compounds play crucial roles in protecting plants from heavy metal toxicity [5,6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…The combination of low kinetic stability and high thermodynamic is the main features of metal-MT complexes, which bind the metals very firmly, while a part of the metal ions is easily exchanged for other proteins (Maret, 2000 ). Transgenic plants overexpressing MTs genes have been scored for enhanced metal tolerance and they demonstrate modified metal accumulation or distribution strategies (Gu et al, 2015 ; Liu et al, 2015a ; Tomas et al, 2015 ). In plants, vacuole is considered as the final destination of detoxification of HMs.…”
Section: Heavy Metals (Hms) Detoxificationmentioning
confidence: 99%
“…Phytochelatins (PCs) and metallothioneins (MTs) are the most well-characterized heavy metal-binding ligands in plants. Numerous reports have shown that MTs play crucial roles in maintaining metal homeostasis and protect against heavy metal toxicity through intracellular sequestration [1][2][3][4][5].…”
mentioning
confidence: 99%